Internalisasi Pendidikan Kristiani Melalui Pembinaan Mental Spiritual Pada Prajurit TNI Angkatan Darat Kodam XIII Merdeka Manado - Merry Regina Mamuko; Esther Heydemans; Wolter Weol (Peneliti.net, 2021)
Indonesian National Army (TNI). The TNI is one of the state apparatuses that concentrates and carries out tasks on the defense and security of the sovereignty of the territory of the Unitary State of the Republic of Indonesia (NKRI). The professionalism of TNI-AD Soldiers is solid, one of which is motivated by a solid mental condition as well as one of its elements. Mental-spiritual development is an effort made by the TNI in equipping soldiers for the internalization of Christian education in the lives of soldiers. This can be seen from TNI soldiers who become special servants of the congregation such as elders, deacons, head of the fathers, and so on. But on the other hand there are TNI personnel who are involved in fights, violence, and other problems. The purpose of this study is to explain and assess the absorption of Christian education through mental and spiritual growth for Indonesian Army soldiers at the Merdeka XIII Kodam: (1) internalization of Christian education through mental and spiritual development of TNI soldiers at Kodam XIII Merdeka Manado, (2) the impact of internalizing Christian values through mental and spiritual development for TNI soldiers at the Merdeka Manado Military Command XIII, and (3) supporting and inhibiting factors for internalizing Christian education values through mental and spiritual development for TNI soldiers at the Merdeka Manado Military Command XIII. This is a qualitative research project. Interview, observation, and documentation criteria were employed to obtain data. The findings revealed that (1) the internalization of Christian education values through mental and spiritual development of Indonesian Army soldiers at Kodam XIII Merdeka Manado can be divided into four categories, namely worship using the lecture method, counseling guidance, counseling in conveying Christian values, nationality, and struggle; and services for soldiers who request them. (2) The impact of internalizing Christian education ideals through mental growth of TNI-AD soldiers of Merdeka Military Command XII Manado, namely, soldiers who are obedient and believe in God. The second step is to create a Christian environment. The next step is to establish a disciplined military environment. Fourth, in a soldie's life, the achievement of a happy family. (3) The shortage of experts, the inability to reach soldiers directly, and the soldiers' lack of knowledge of the importance of cooperating and being open are all problems that impede the absorption of Christian education values. Continuous activities, publication of bulletins, magazines, and troof info (brochures), attention and encouragement from commanders, and the availability of facilities in the implementation of mental-spiritual development activities are all supporting factors in internalizing the values of Christian education through mental-spiritual development.